2017
DOI: 10.1002/chem.201703051
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Shielding Studies of C2 and C2H2 Support Higher than Triple Bond Multiplicity in C2

Abstract: The carbon-carbon bonds in the ground states of C 2 and C 2 H 2 , at their equilibrium geometries, are compared by analysing the changes in the off-nucleus magnetic shielding tensor within the space surrounding each of these molecules. A wide range of quantum-chemical approaches, including full-valence CASSCF-GIAO, CCSD(T)-GIAO and CCSDT-GIAO, all with the cc-pVQZ basis set, as well as HF-GIAO and MP2-GIAO, with the cc-pVQZ, cc-pV5Z and cc-pV6Z basis sets, show that the surroundings of the carbon-carbon bond i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
10
25
0
Order By: Relevance
“…Based on the results obtained here, as well as literature data [1][2][3][4][5][6][7][8][9], some conclusion can be pointed out:…”
Section: Resultssupporting
confidence: 65%
“…Based on the results obtained here, as well as literature data [1][2][3][4][5][6][7][8][9], some conclusion can be pointed out:…”
Section: Resultssupporting
confidence: 65%
“…The energy of this “inverted bond” was found of about 20 kcal/mol. This conclusion is supported by the compared magnetic shielding of C 2 and acetylene and also by a recent study using a symmetry‐broken wave function, yielding to an effective bond order of 3.36 …”
Section: Resultssupporting
confidence: 61%
“…In this paper we study bonding and aromaticity in the ground, first singlet excited and lowest triplet electronic states of S 2 N 2 by analysing the changes in the off‐nucleus magnetic shielding tensor, σ ( r ), within the space surrounding the molecule. Previous research on carbon–carbon bonds showed that the off‐nucleus isotropic magnetic shielding, σiso(boldr)=13[σxx(r)+σyy(r)+σzz(r)] , is capable of exposing the differences between carbon−carbon bonds of different multiplicities in much greater detail than is achievable using the total electronic density. One of our aims is to establish whether the variations in σ iso ( r ) provide similar insights into the nature of the S−N bond in S 2 N 2 .…”
Section: Introductionmentioning
confidence: 86%